(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Agriculture in the 21st century will keep on confronting various, between associated difficulties everywhere throughout the world. It must deliver more food to bolster a developing populace portrayed by changing utilization patterns, and dietary and nourishing inclinations. Food and Agriculture Organization (FAO) moderately anticipated that if the worldwide populace achieves 9.1 billion by 2050, world production should ascend by 70, and food production particularly in the developing scene should twofold. In Africa, which will make up a more prominent offer of the worldwide populace, demand may get tripled by 2050. Agriculture faces uncommon formative difficulties all inclusive. In the meantime, fast advances in agricultural research and development at the worldwide, territorial and national dimensions, offer exceptional chances, enhancing performance over the whole agriculture product value chain. The examination uncovers the commitment of expanded agricultural productivity in food security in the developing countries. Food security is a need for each person, home, network and country. In developing countries, food security could be substantially enhanced by expanded investment and strategy changes. In this article, we studied about the concept of Food Security and the relation between Poverty, food security and Agricultural Productivity through a review study.